Disease-related knowledge and smoking behavior of patients with Crohn's disease. Issue 9 (September 2016) - Li, Guanwei; Ren, Jianan; Wang, Gefei; Hu, Qiongyuan; Wu, Qin; Wu, Xiuwen; Li, Ranran; Guo, Kun; Li, Yuan; Gu, Guosheng; Ren, Huajian; Hong, Zhiwu; et al.
Abstract: Background: Patients' knowledge poses effects on quality of life, treatment adherence and coping skills in the management of Crohn's disease. Smoking is the most established risk factor and associated with a more severe course. Aims: We aimed to investigate the status of patients' knowledge on Crohn's disease in China, and explore the relationship between patients' knowledge and smoking behavior. Methods: Web-based questionnaires were created including a validated Crohn's and Colitis Knowledge Score applied to all participants and the Fagerström Test for Nicotine Dependence to smokers. The sociodemographic data, disease characteristics and smoking status were recorded. Patients were enrolled through invitation emails and Internet advertising. Current and ex-smokers were re-visited 6 months after enrollment. Results: 923 patients completed valid questionnaires with the knowledge score of 12.18 ± 4.61. Disease duration and educational status were independent predictors of the knowledge score by multiple linear regression analysis. The smoking rate was 8.2%. Low knowledge score was related with smoking behavior but not nicotine dependence, and smoking relapse during 6 months after enrollment. Conclusions: Patients' education should be a priority considering its impacts on many factors including smoking. Extra attention should be given to those from countryside area or having low family income and educational achievement.